Daya Analgetik Fraksi Tak Larut N-Heksana dari Ekstrak Etanol Daun Ketela Rambat (Ipomoea batatas L) pada Mencit yang Diinduksi dengan Etil Asetat - Hastuti, Siwi; Pratama, Bangkit Ary (Indonesian Journal on Medical Science, 2024)
Cassava (Ipomoea batatas L) contains flavonoids, polyphenols and saponins. Cassava leaves have shown analgesic and anti-inflammatory effects in ethanol extract preparations. This study aims to analyze the analgesic activity of the insoluble n-hexane fraction from the ethanol extract of cassava leaves in mice given the pain stimulus of acetic acid. Simplicia extraction was carried out by maceration with 70% ethanol, while fractionation with n-hexane. The test groups were group I (Acetosal 65 mg/kgBW), group II (water as negative control), groups III, IV and V (n-hexane insoluble fraction from ethanol extract of cassava leaves at doses of 25, 50 and 100 mg/kgBW ). Each group was given the test preparation orally, then immediately injected 1% acetic acid intraperitoneally. The mice's movements were recorded every five minutes for one hour. The number of writhes is used to calculate the percentage of analgesic power. The results of the percentage of analgesic power of the test preparations at doses of 25, 50 and 100 mg/kgBW were (12.49 ± 2.00)%, (48.33 ± 1.69)% and (55.62 ± 1.63). )%, while acetosal has an anagetic power percentage of (57.91 ± 0.84)%. The results of the one way Anova test show a p value = 0.000, meaning there is a significant difference. However, in the post hoc test, significant differences were shown between the test treatments except between the test dosage preparation of 100 mg/kgBW and acetosal. Cassava leaves have the potential to be used as a new analgesic medicine.